Relationship between blood urea nitrogen and 28-day all-cause mortality in patients with acute pulmonary edema: a retrospective analysis of the MIMIC-IV database - Tu, Guang; Liu, Yuwen; Huang, Xiaomi; Zeng, Yanfang; Cai, Zhonglan; Wang, Chunyan (Frontiers in Cardiovascular Medicine, 2025)
BackgroundAcute pulmonary edema is a severe clinical syndrome with high mortality. Blood Urea Nitrogen (BUN) levels, which indicate renal function and metabolic state, may have prognostic value in critically ill patients. However, their relationship with outcomes in acute pulmonary edema remains unclear.ObjectiveThis study aims to investigate the association between admission BUN levels and 28-day all-cause mortality in patients with acute pulmonary edema.MethodsThis retrospective cohort study utilized data from the Medical Information Mart for Intensive Care IV (MIMIC-IV) database, covering the period from 2008–2019. It included adult patients diagnosed with acute pulmonary edema. Patients were divided into four groups based on their BUN levels. Cox regression models, restricted cubic spline (RCS) curves, Kaplan–Meier analysis, and subgroup analyses were used to assess the relationship between BUN levels and mortality.ResultsA total of 1,094 patients were included in the study. Univariate Cox regression analysis revealed a positive correlation between BUN levels and 28-day mortality (HR = 1.02, 95% CI: 1.01–1.02, P < 0.001). Multivariate analysis confirmed BUN as an independent predictor of mortality (HR = 1.02, 95% CI: 1.01–1.02, P < 0.001). The RCS curve indicated a nonlinear relationship, and Kaplan–Meier analysis showed lower survival in the higher BUN groups (P < 0.001). Subgroup analysis found the association to be significant across all subgroups.ConclusionAdmission BUN levels predict 28-day all-cause mortality in patients with acute pulmonary edema. Clinically, BUN monitoring should be emphasized, and individualized prognostic and treatment strategies should be developed to improve outcomes.